Oxytocin receptor: Expression in the trigeminal nociceptive system and potential role in the treatment of headache disorders. (September 2016) - Tzabazis, Alexander; Mechanic, Jordan; Miller, James; Klukinov, Michael; Pascual, Conrado; Manering, Neil; Carson, Dean S; Jacobs, Allon; Qiao, Yanli; Cuellar, Jason; Frey, William H; Jacobs, Daniel; et al.
Aims: Our studies investigated the location of oxytocin receptors in the peripheral trigeminal sensory system and determined their role in trigeminal pain. Methods: Oxytocin receptor expression and co-localization with calcitonin gene-related peptide was investigated in rat trigeminal ganglion using immunohistochemistry. Enzyme-linked immunosorbent assay was used to determine the effects of facial electrocutaneous stimulation and adjuvant-induced inflammation of the temporomandibular joint on oxytocin receptor expression in the trigeminal ganglion. Finally, the effects of oxytocin on capsaicin-induced calcitonin gene-related peptide release from dural nociceptors were investigated using isolated rat dura mater. Results: Oxytocin receptor immunoreactivity was present in rat trigeminal neurons. The vast majority of oxytocin receptor immunoreactive neurons co-expressed calcitonin gene-related peptide. Both electrocutaneous stimulation and adjuvant-induced inflammation led to a rapid upregulation of oxytocin receptor protein expression in trigeminal ganglion neurons. Oxytocin significantly and dose-dependently decreased capsaicin-induced calcitonin gene-related peptide release from dural nociceptors. Conclusion: Oxytocin receptor expression in calcitonin gene-related peptide containing trigeminal ganglion neurons, and the blockade of calcitonin gene-related peptide release from trigeminal dural afferents suggests that activation of these receptors may provide therapeutic benefit in patients with migraine and other primary headache disorders.